Produção científica em retinopatia da prematuridade: um estudo bibliométrico do fator de risco para alterações visuais - Nunes, Ana Carolina (2012)
Early identification of risk factors for changes in development enables the implementation process of early intervention and prevention of aggravations. Among these risk factors are prematurity. Prematurity is considered the main cause of death, morbidity and disability for children, triggering a series of risk factors for development, leading to the emergence of several clinical problems, being an important risk factor for the vision development. Among the problems presented by the premature newborn is Retinopathy of Prematurity (ROP), a vasoproliferative disease and leading cause of infant blindness. This research aimed to identify studies on ROP consolidated in theses and dissertations and scientific articles produced in Brazil in view of construct bibliometric indicators enabling to describe and analyze the scientific production from the perspective of Special Education. To develop the study, was used the methodological approach of bibliometrics from searches for pre-defined keywords. Theses and dissertations from thesis Bank of CAPES and scientific papers present in SciELO database were investigated, focused in Retinopathy of Prematurity. A total of 41 theses and dissertations and 33 articles were located, being the studies classified according to the nature, in principal and secondary. The results reveal that most of the studies on theses and dissertations related to subject of ROP are concentrated in Southeast region of Brazil. The interest in ROP research increased over the years, however these studies focus still in biomedical area, with newborns. A lack of studies in education area was identified, especially in Special Education. Is suggested the development of future studies in this field with children of different ages, in order to identify the impact of ROP on literacy / education of these children.